Determinants of Attitudes Towards Web Advertising: An Evidence from Malaysia - Rahimi, Nur Syuhada; Mohamad, Assoc. Prof. Dr. Bahtiar; Alhaiou, Talhat; Raza, Syed Hassan (Jurnal The Messenger, 2019)
The purpose of this study is to examine the factors which influence of the consumer s Attitudes Towards Web Advertisement (ATWA). Drawing conceptual framework from Elaboration Likelihood Model (ELM), the influence of the six independent variables have been analyzed in this study, including informativeness, entertainment, credibility, economic value, interactivity, and materialism. The data has been obtained from 384 Honda users by using online questionnaires. Results of multiple regression analysis have revealed that all six factors influenced the attitude towards Honda web advertising. However, it has been revealed that the informativeness is a most important predictor of the ATWA. This study has shown that Elaboration Likelihood Model is interrelated with the determinants of consumer's attitudes towards Honda web advertisement and offered managerial implication.